Teachers’ Perceptions of Their Role and Classroom Management Practices in a Technology Rich Primary School Classroom - Johler, Minttu; Krumsvik, Rune Johan; Bugge, Hans Erik; Helgevold, Nina (Frontiers in Education, 2022)
This case study investigates primary school teachers’ perceptions of their role and pedagogical practices in regard to classroom management in technology-rich classrooms. The data was collected through individual and focus group interviews, observation and a survey at a school where implementation of digital technologies has had a high priority over several years. The study identifies complexity and contemporary elements in teachers’ perceived role and pedagogical practices, as the rapid evolution of ICT requires teachers to constantly keep up-to-date, gain new competencies and evaluate their practices to be able to facilitate learning in physical classrooms that have expanded to the digital space. In this process, the role of leadership, collegial collaboration, good teacher-pupil relationships and teachers’ ability to adapt and take up a role of a learner have been found pivotal.